The Effect of Using Game Based Learning Quizizz Media on Increasing Student Motivation and Learning Outcomes of 6th grade in science subjects at 125 Taruna Karya Elementary School Bandung - Mustaqim, Aris (International Conference on Elementary Education, 2024)
This study  aims to determine the effect of using Quizizz on the motivation and learning outcomes of 6th grade students at SDN 125 Taruna Karya Kota Bandung in science subject by using Quizizz media based on game based learning. The research method in this study is the a Pre-Experimental method which observes a main group and intervenes throughout the study without a control class. The subject of this study was 6th grade which consisted of 30 students. This research was conducted in two meetings before and after being given treatment by filling out a motivational learning questionnaires and evaluating learning outcomes. The instruments used are questionnaires and learning outcomes tests. The method used in data analysis is the quantitative description analysis method. The results showed that there was an increase in motivation and learning outcomes of 6th grade in science subjects at SDN 125 Taruna Karya Kota Bandung  by using Quizizz media. This can be proven by using the Paired Sample T Test, there is an increase in learning motivation from an average of 41.60 to 48.93, meaning an increase of 7.33. As for learning outcomes in the cognitive aspect, there was an increase from an average value of 64.37 to 75.57, meaning an increase of 11.2.